PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN SEBAGAI PENENTU PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR - Suprihati; Wilhelmus Datong Kelore; Darmanto (Media Akuntansi, 2021)
Companies in Indonesia have a number of adverse impacts due to the company's operations, so companies need to take responsibility by disclosing Corporate Social Responsibility (CSR). This study aims to examine the effect of profitability, leverage, company size, and company growth on CSR disclosure. The population of data in this study were 144 manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2018 period and a sample of 40 companies. The selection of this sample uses a purposive sampling method. The data source is taken from www.idx.co.id. Data analysis of this study uses multiple linear regression which results that variable company size has a positive and significant effect on CSR disclosure, while profitability, leverage and company growth variables have no significant effect on CSR disclosure..